Experimental and theoretical investigation of FeCrVAl and related compounds. (1st January 2023) - Lukashev, Pavel V; Stuelke, Lukas; Pottebaum, Zach; Moua, Young; Baker, Gavin; Wysong, Jax; Flesche, Matthew; Valloppilly, Shah; Shand, Paul M; Kharel, Parashu
Abstract: We have carried out a combined theoretical and experimental investigation of FeCrVAl, and the effect of Mn and Co doping on its structural, magnetic, and electronic band properties. Our first principles calculations indicate that FeCrVAl, FeCr0.5 Mn0.5 VAl, and FeCr0.5 Co0.5 VAl exhibit nearly perfect spin polarization, which may be further enhanced by mechanical strain. At the same time, FeCrV0.5 Mn0.5 Al and FeCrV0.5 Co0.5 Al exhibit a relatively small value of spin polarization, making them less attractive for practical applications. Using arc melting and high vacuum annealing, we synthesized three compounds FeCrVAl, FeCr0.5 Mn0.5 VAl, and FeCr0.5 Co0.5 VAl, which are predicted to exhibit high spin polarization. The room temperature x-ray diffraction patterns of all samples are fitted with full B2 type disorder with a small amount of FeO2 secondary phase. All samples show very small saturation magnetizations at room temperature. The thermomagnetic curves M(T) of FeCrVAl and FeCr0.5 Co0.5 VAl are similar to that of a paramagnetic material, whereas that of FeCr0.5 Mn0.5 VAl indicates ferrimagnetic behavior with the Curie temperature of 135 K. Our findings may be of interest for researchers working on Heusler compounds for spin-based electronic applications.